Design And Development of a Nationwide Centralized Blood Bank System for Efficient Blood Donation and Distribution - Basheer Riskhan; Abdullahi Mohamed Ali; Ibrahim Osman Sheikh Hussein; Abdirahman Ibrahim Osman; Siva Raja Sindiramutty; Noor Zaman Jhanjhi (Journal of ICT, Design, Engineering and Technological Science, 2026)
A centralized digital system, the Nationwide Centralized Blood Bank System (NCBBS), is proposed to address operational inefficiencies in blood donation and distribution in Sri Lanka, driven by decentralization and semi-manual processes. Although a well-founded National Blood Transfusion Service (NBTS) and a well-established voluntary donor culture are in place, a lack of real-time nationwide visibility into blood stocks leads to shortages, wastage, and delays in emergency situations. This report describes the design and development of a centralized, web-based application that integrates donor registration, health screening, laboratory testing, blood unit management, request processing, and emergency prioritization into a single, secure system. The system uses an Agile System Development Life Cycle (SDLC) and a layered multi-tier architecture comprising presentation, business logic, data management, and security layers. A role-based access control model with eight user roles implements accountability for operations and data in accordance with the Personal Data Protection Act in Sri Lanka. Modular system design helps in scalability, maintainability, and integration of predictive analytics and decision support in the future. Nationwide blood bank management through consolidation of stakeholders, such as blood collectors, blood storage facilities, requester organizations, and administrators into a single coordinated ecosystem, NCBBS promotes transparency, enhances inter-institutional coordination, and creates a safe platform on which nationwide blood bank management can be realized in accordance with international best practices of digital health.